Improving Elementary Students’ Reading Comprehension through Guided Reading in TaRL Instruction - Yuyun Dwi Suryandari; Nunung Suryati; Ahmad Heki Sujiatmoko (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The objective of the research was to improve elementary school students’ reading comprehension skills through the implementation of the Guided Reading strategy in TaRL instructional framework. Adopting a Classroom Action Research (CAR) design, executed through a singular cycle, of four teaching sessions incorporating all eight sequential stages of the Guided Reading approach. Participants were stratified into Group A and Group B according to baseline reading proficiency levels. Quantitative data were subjected to analysis via descriptive statistics and one-sample t-test, utilizing the Minimum Mastery Criterion (KKM) set at 85. The findings of the study reveal a notable enhancement in reading comprehension skills among both groups. In Group A, students met the Minimum Mastery Criterion increased from 0/12 in the initial test to 12/12 in Cycle I, and Group B, from 3/15. These outcomes indicate that the application of the Guided Reading methodology within the TaRL framework significantly contributes to the improvement of reading comprehension skills among students with initially stronger abilities.